Unmanned aircraft systems - Gupta, Sachin Kumar (Scrivener Publishing, 2025)
This book is an essential resource for anyone looking to understand the cutting-edge applications and evolving technologies of Unmanned Aerial Systems, showcasing how they enhance safety and efficiency in monitoring, emergency response, and smart city development. With the evolution of Unmanned Aircraft Systems (UAS), its applications can be observed in the fields of monitoring for fire detection, sustainable computing, emergencies, and law enforcement. They can be useful for monitoring or screening applications, as well as the deployment of smart cities, security monitoring, and communication establishments at rare locations or unapproachable locations. Thus, the wireless ad-hoc networks of Unmanned Aerial Vehicles (UAVs) and infrastructure-based UAVs can be utilized in this proposal. Unmanned aircraft systems (UAS) extend human potential and allow us to execute dangerous or difficult tasks safely and efficiently, saving time, money, and, most importantly, lives. UAS can help police, fire, and other public workers save lives in emergencies like natural disasters, locate missing animals and children, or help fight fighters. Unmanned Aircraft Systems contains novel contributions and emerging trends in the area of Unmanned Aerial Vehicles (UAV), drones, and aircraft without a human pilot aboard. It has three segments incorporating technological advancements and future trends in UAS, the policies and security aspects of UAVs, and their applications as an intelligent system. Along with these state-of-the-art techniques, this book also incorporates advances in AI and machine learning, deep learning, IoT technology, cybersecurity and Blockchain, UAV regulation policies in the United States and Europe, SOTA in ITS, and many more technological advancements, which makes this book the pioneer and benchmarking reference in these areas
Keywords: Maschinenbau, Fertigungstechnik